2018
DOI: 10.1111/grow.12242
|View full text |Cite
|
Sign up to set email alerts
|

Does Shale Energy Development Mean More Crime? The Case of the Bakken Oil Boom

Abstract: The rise and fall of shale oil production in recent years have led to tremendous economic growth and challenges to shale communities in the U.S. In this study, we attempt to address the inconsistent results in previous studies and shed light on the relationship between rural crimes and shale oil development at the Bakken using county‐level data for Montana and North Dakota from 2000 through 2014. Our results indicated statistically significant evidence of increased aggravated assaults, burglaries, larcenies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…We find mixed results depending on the regions and time periods considered, highlighting the importance of conducting region-specific analysis when evaluating the impact of the recent boom in the unconventional oil and gas sector. Our findings are overall consistent with previous studies that found increased drilling activities and shale gas developments to have improved the economic outcomes in the participating regions in the short-term (e.g., Agerton et al, 2017;Brown, 2014;Munasib & Rickman, 2015;Weber, 2012Weber, , 2014, while negatively affects some economic measures in the long run (e.g., Jackson et al, 2013;Lim, 2018;Maguire & Winters, 2017;Rich et al, 2014).…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We find mixed results depending on the regions and time periods considered, highlighting the importance of conducting region-specific analysis when evaluating the impact of the recent boom in the unconventional oil and gas sector. Our findings are overall consistent with previous studies that found increased drilling activities and shale gas developments to have improved the economic outcomes in the participating regions in the short-term (e.g., Agerton et al, 2017;Brown, 2014;Munasib & Rickman, 2015;Weber, 2012Weber, , 2014, while negatively affects some economic measures in the long run (e.g., Jackson et al, 2013;Lim, 2018;Maguire & Winters, 2017;Rich et al, 2014).…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…However, along with the positive impacts, fracking also created negative externalities to shale‐producing regions. Some of these externalities discussed in the literature include, among others, increased crime rate, rising noise level, disruption to the wildlife, threats to the environment and health, and negative impacts on residents' well‐beings and college completion rates (e.g., Jackson et al, 2013; James & Smith, 2017; Komarek, 2018; Lim, 2018; Maguire & Winters, 2017; Rich et al, 2014; Rickman et al, 2017). Overall, the existing literature suggests that a comprehensive approach that accounts for various aspects of the economy is needed when evaluating the net impact of shale development.…”
Section: Impact Of Marcellus and Utica Shale Developmentmentioning
confidence: 99%
“…Most boomtown scholarship since 2005 reports that increases in crime are associated with the types of public order offenses involving large numbers of young men abusing alcohol and drugs, such as assaults, disorderly conduct, and impaired driving (Lim, 2018;Montana All Threat Intelligence Center, Montana Board of Crime Control, 2014;North Dakota State and Local Intelligence Centre, 2012). In terms of crimes against persons, the number of assault cases processed by North Dakota courts grew by over four-fifths (82%) between 2002 and 2014 while the population grew by less than one-fifth (Ruddell, 2017).…”
Section: The Boom-crime Relationshipmentioning
confidence: 99%
“…Historically, boomtowns are a label for communities undergoing rapid development as a result of hunting and mining (Ruddell, 2017). In total, 64% (N=16 of 25) of the outputs in this investigation referenced boomtowns to justify testing the correlation between shale gas development and crime (i.e., Berger and Beckmann, 2010;Gourley and Madonia, 2017;Haggerty et al, 2014;James and Smith, 2017;Jones, 2016;Komarek, 2018, Lim, 2018Luthra et al, 2007;O'Connor, 2017;Poirrier, 2016;Price et al, 2014, Putz et al, 2011Raimi, 2012;Rhubart and Brasier, 2019;Ruddell et al 2014;Stretesky et al, 2018).…”
Section: Theoretical Contextmentioning
confidence: 99%
“…Sixty percent (N=15 of 25) outputs selected for study in this analysis rely, at least partly, on social disorganization as a theoretical framework to hypothesize that shale gas development increases crime (i.e., Berger and Beckmann, 2010;Deller and Schreiber, 2012;Gourley and Madonia, 2017;Haggerty et al, 2014;James and Smith, 2017;Jones, 2016;Lim, 2018;Luthra et al, 2007;O'Connor, 2017;Poirrier, 2016;Putz et al, 2011;Raimi, 2012;Rhubart and Brasier, 2019;Ruddell et al, 2014;Stretesky et al, 2018). While most of these outputs focus on serious crimes such as murder, rape, assault, robbery, burglary, larceny and motor vehicle theft, the notion of social disorder type violations such as drunk driving, drunkenness, drug abuse, illegal gambling, liquor law violations, disorderly conduct and vagrancy were also mentioned (i.e., Andrews and Deza, 2016;Beleche and Cintina, 2018;Jacquet, 2015;Jones, 2016;Komarek, 2018;Raimi, 2012;Rhubart and Brasier, 2019;Ruddell et al, 2014).…”
Section: Theoretical Contextmentioning
confidence: 99%